The Influence of Halal Factors and Behavioral Constructs on Culinary Business Governance in South Sulawesi - Mashur Naufal Hamid; Abdul Hamid Habbe; Ihya Ulumuddin; Alif Razaq Aryadi (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study examines the influence of halal awareness, halal certification, and behavioral factors on the governance of halal culinary businesses in South Sulawesi, Indonesia. With the increasing emphasis on halal certification following national regulatory mandates, business actors—particularly micro, small, and medium enterprises (MSMEs)—continue to face challenges such as distrust in certification bodies, the complexity of certification procedures, and limited access to accurate information. Grounded in the Theory of Planned Behavior (TPB), this research introduces trust in halal certification and halal products as a mediating variable. A quantitative approach was employed using a survey of 400 halal culinary entrepreneurs from major cities in South Sulawesi, including Makassar, Gowa, Maros, and Parepare. Data were collected using a 5-point Likert scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings are expected to identify key determinants influencing the sustainability of halal culinary businesses and provide practical recommendations for policymakers and stakeholders to enhance trust and improve governance effectiveness within Indonesia's growing halal economy.